2014
DOI: 10.1111/joor.12193
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term subjective tongue function after partial glossectomy

Abstract: There have been limited studies of subjective tongue function over long-term follow-up in spite of swallowing and articulation disorders are common complications of glossectomy. To assess long-term subjective swallowing and articulation function after partial glossectomy. A total of 63 patients with the mobile tongue cancer who underwent partial glossectomy without reconstruction were interviewed to score their swallowing and articulation function on a 100-point scale. The relation of this subjective scoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
4
9
1
1
Order By: Relevance
“…They found a significantly better functional outcome for the non-reconstructed patients. These results are in line with data published from some other centers investigating the role of oral and oropharyngeal reconstruction [15,16]. When the resection is larger the literature is more supportive towards reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…They found a significantly better functional outcome for the non-reconstructed patients. These results are in line with data published from some other centers investigating the role of oral and oropharyngeal reconstruction [15,16]. When the resection is larger the literature is more supportive towards reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…However, while the variation in asymmetry increases with T-stage and type of treatment, the median does not, which is largely in line with the rest of the results. The same can be found in other literature such as Zuydam et al[8] where speech scores after surgery are overlapping between T-stages or did not yield significant correlation with speech function[8,10]. Furthermore, it is shown in previous literature that post-operative impairment not only depends on the size and location of the treatment but also on the amount of scar tissue and compensatory tongue motion patterns[12,14].…”
Section: Discussionsupporting
confidence: 75%
“…Surgical treatment of lateral tongue carcinoma often leads to asymmetrical tongue movements[6,7]. With increasing T stage this impairment becomes more outspoken and is accompanied by deterioration of speech quality and mastication function[810]. The organ sparing surgical chemoradiation is usually the preferred treatment for base of the tongue tumors, but in advanced cases this modality may also lead to serious functional deficits with more impact on swallowing than surgery of the mobile tongue[3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding tongue reconstruction after partial glossectomy, previous studies have reported only functional outcomes of one reconstructive method and con icting results about the optimal reconstructive method. A long-term follow-up study of 63 patients with partial glossectomy of the tongue appeared good speech and swallowing function without ap reconstruction [17]. A prospective multicenter study also reported that the postoperative speech and swallowing function were better following a primary closure compared to a free ap reconstruction for a partial glossectomy [18].…”
Section: Discussionmentioning
confidence: 97%